Low-dielectric OCA (Optical Clear Adhesive) as well as preparation method and application thereof

By introducing a modified functional agent, the molecular structure and chemical composition of OCA optical glue is optimized, and the limitations of traditional OCA optical glue in terms of dielectric properties, adhesive properties and aging resistance are solved, and low dielectric constant, high peeling force and superior aging resistance are achieved, which is suitable for high-end display technology.

CN119529682APending Publication Date: 2025-02-28ANHUI ZHIYAN CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411759189.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional OCA optical adhesives have limitations in dielectric properties, adhesive properties and aging resistance, especially in the field of folding display technology, which is difficult to meet high performance needs.

Method used

By introducing a modified functional agent, the molecular structure and chemical composition of OCA optical glue are optimized, the dielectric constant is reduced, and the peeling force, impact resistance and bonding strength are improved.

Benefits of technology

It achieves low dielectric constant, high peeling force, impact resistance and superior aging resistance, and is suitable for high-end applications such as folding display terminals.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a low-dielectric OCA (Optical Clear Adhesive) as well as a preparation method and application thereof, and belongs to the technical field of OCA, the preparation method of the low-dielectric OCA comprises the following steps: mixing an acrylate monomer, a modified functional agent and other additives according to a specific proportion, and carrying out ultraviolet curing to form the optical cement. Compared with the prior art, the low-dielectric OCA optical cement disclosed by the invention has excellent mechanical strength, toughness and adhesive property while maintaining the low dielectric property. Excellent optical transparency and ultraviolet resistance are shown, the reliability and durability of the product are improved, and the application range of the product in the high-performance display technology is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of OCA optical adhesives, and in particular to a low-dielectric OCA optical adhesive and a preparation method and application thereof. Background Art

[0002] As modern electronic devices develop towards thinness and high performance, the performance requirements for optical adhesive materials in the field of display technology are increasing. Especially in high-end applications such as folding displays and touch screens, higher standards are put forward for the optical, mechanical and electrical properties of optical adhesives. As a key bonding material, optically clear adhesive (OCA) is widely used in the manufacturing process of liquid crystal displays, touch screens, smart phones, tablet computers and other devices. Its performance directly affects the display effect and service life of the product.

[0003] Traditional OCA optical adhesives are mainly based on acrylates and are cured through photocuring technology. However, these materials have limitations in dielectric properties, bonding properties, and aging resistance. Especially in the field of folding display technology, the high dielectric constant of traditional OCA optical adhesives limits touch sensitivity and signal transmission speed, while its aging resistance and impact resistance are also difficult to meet the needs of long-term use. In addition, as the frequency of device use increases, the peel force and bonding strength of traditional OCA optical adhesives are insufficient, which can easily lead to problems such as debonding, bubbles, and creases during device use.

[0004] Although there have been some improvement measures for the above problems, such as improving the UV resistance by adding anti-UV agents, these improvements often come at the expense of other properties and it is difficult to achieve a comprehensive improvement in comprehensive performance. Therefore, the development of an OCA optical adhesive with low dielectric, high adhesion and excellent aging resistance is of great significance to the development of display technology.

[0005] Chinese invention patent CN113322028A discloses a UV-resistant OCA optical adhesive, comprising the following raw materials in parts by weight: 10 to 60 parts of acrylic pressure-sensitive adhesive, 0.1 to 1 parts of ultraviolet absorber, 0.001 to 0.1 parts of curing agent, and 30 to 80 parts of solvent; the ultraviolet absorber is 2-(2'-hydroxy-5'-heptylphenyl)benzotriazole. The invention also discloses a UV-resistant OCA optical adhesive film, which is obtained by coating and curing the UV-resistant OCA optical adhesive in sequence. The OCA optical adhesive of the invention not only has excellent anti-ultraviolet effect, but also the curing degree of the optical adhesive film formed can reach 100%, thereby ensuring that the OCA optical adhesive film has excellent anti-UV effect on the basis of complete curing of the adhesive layer. However, the OCA optical adhesive prepared by the invention has poor adhesion and aging resistance and is easy to peel off. Summary of the invention

[0006] In view of the limitations in the prior art, the present invention aims to provide a low dielectric OCA optical adhesive and a preparation method and application thereof. By introducing a modified functional agent, the molecular structure and chemical composition of the OCA optical adhesive are optimized to achieve low dielectric constant, high peel force, impact resistance and excellent aging resistance, thereby meeting the demand for high-performance OCA optical adhesive in fields such as folding display technology.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a low dielectric OCA optical adhesive is as follows, in parts by weight: Step 1, first, 60-80 parts of butyl acrylate, 15-25 parts of allyl 2-hydroxypropionate, 8-12 parts of 2-ethylhexyl acrylate, 0.04-0.06 parts of α,α-dimethoxy-α-phenylacetophenone and 0.03-0.05 parts of n-dodecyl mercaptan are mixed in a three-necked flask, stirred for 20-40 minutes in a nitrogen environment, and then irradiated with an ultraviolet lamp to obtain an acrylate polymer; Step 2: 80-120 parts of the acrylate polymer prepared in step 1, 4-6 parts of a functional modification agent, 5-10 parts of 1-ethyl cyclohexyl acrylate, 0.3-0.5 parts of 1,10-decanediol diacrylate, 5-10 parts of 3-isobornyl cyclohexyl acrylate, 8-12 parts of diethylene glycol monoacrylate, 0.1-0.3 parts of hydrogenated rosin, 0.2-0.4 parts of an antioxidant, 0.5-1 parts of a photoinitiator and 0.5-1 parts of dibenzoyl peroxide are mixed and allowed to stand to eliminate bubbles, and then a 60-100 um thick adhesive layer is evenly coated on the light release protective film using an automatic coating machine, and a layer of heavy release protective film is covered, and ultraviolet light is used for curing to obtain a low dielectric OCA optical adhesive.

[0008] The ultraviolet light irradiation in step 1 is to use an ultraviolet light with a wavelength of 350-400nm for 1-5 minutes, and the ultraviolet light energy is 600-1000mJ / cm 2 .

[0009] The UV curing in step 2 is performed by using UV light with a wavelength of 350-400 nm for 1-5 minutes, and the UV light energy is 800-1200 mJ / cm 2 .

[0010] The antioxidant is at least one of antioxidant 1076, antioxidant 168, antioxidant 703, and antioxidant 1010.

[0011] The photoinitiator is at least one of photoinitiator 1173 and photoinitiator 754 .

[0012] The light release protective film has a thickness of 30-60 μm and a release force of 4-6 g / in.

[0013] The heavy release protective film has a thickness of 50-100 μm and a release force of 20-30 g / in.

[0014] The preparation method of the modified functional agent is as follows, in parts by weight: S1. Mix 200-400 parts of dimethyl sulfoxide, 120-180 parts of methanol, 12-18 parts of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 5-7 parts of pentafluorophenylpropyltrimethoxysilane in a flask, add 5-10 parts of potassium carbonate, heat to 140-160° C. for azeotropic dehydration for 1-3 hours, then heat to 160-200° C. for 5-15 hours, then cool and add 300-500 parts of anhydrous ethanol, obtain a filter cake by suction filtration and washing, and finally dry to obtain a pretreated product; S2, heating 30-50 parts of 4-amino-3-hydroxypyridine hydrochloride to 120-140° C. in a flask, adding 5-7 parts of the pre-treated material prepared in step S1, and continuing to heat to 220-240° C. for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated material; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 0.01-0.03 parts of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 12-18 parts of triglycidyl p-aminophenol are added and heated to 120-180° C. for 5-15 hours, washed with 0.2-0.4 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent.

[0015] The low dielectric OCA optical adhesive is applied to a foldable display terminal.

[0016] The reaction mechanism of the present invention involves etherification reaction of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene with pentafluorophenylpropyltrimethoxysilane to obtain a pre-treated product, followed by demethylation reaction of 4-amino-3-hydroxypyridine hydrochloride to obtain a post-treated product. Finally, the hydroxyl group is used as a polymerization initiation site to carry out a ring-opening polymerization reaction with triglycidyl p-aminophenol, and a polyether segment is successfully introduced into the molecular side chain of pentafluorophenylpropyltrimethoxysilane to prepare a modified functional agent.

[0017] The present invention significantly improves the peeling force, impact resistance and bonding strength of low-dielectric OCA optical adhesive by introducing a modified functional agent having a flexible siloxane main chain and a rigid polyphenylene ether side chain. The side chain of the modified functional agent contains a polyether molecular chain, which has excellent compatibility with the acrylate polymer and can form a molecular chain entanglement and physical cross-linking network, effectively absorbing and transmitting stress, thereby improving the mechanical strength and toughness of the adhesive, and expanding its application range in fields such as high-performance display technology.

[0018] The functions of each substance in the present invention are as follows: Butyl acrylate, as one of the acrylate monomers, is used to form the main chain of the acrylate polymer and has an important influence on the physical and chemical properties of the final OCA optical adhesive.

[0019] Allyl 2-Hydroxypropionate is a hydroxyl-containing acrylic acid ester monomer that participates in the polymerization reaction and increases the crosslinking degree and cohesion of the polymer.

[0020] 2-Ethylhexyl acrylate Another acrylate monomer that affects the flexibility and adhesive properties of the polymer.

[0021] α,α-Dimethoxy-α-phenylacetophenone photoinitiator, used to initiate the polymerization reaction of acrylate polymers.

[0022] n-Dodecanethiol may act as a chain transfer agent or cross-linking agent, affecting the molecular weight and cross-linking structure of the polymer.

[0023] 1-Ethyl cyclohexyl acrylate monomer is used to adjust the flexibility and adhesion of the polymer.

[0024] 1,10-Decanediol diacrylate is a bifunctional monomer used to increase the crosslinking density of the polymer.

[0025] 3-Isobornylcyclohexyl acrylate Acrylate monomer that provides specific bonding properties and chemical resistance.

[0026] Diethylene glycol monoacrylate is a difunctional monomer that increases the flexibility and cross-linking degree of the polymer.

[0027] Hydrogenated rosin natural resin, may be used to adjust the viscosity and processing properties of adhesives.

[0028] Antioxidants protect polymers from oxidative degradation during processing or use.

[0029] Photoinitiators promote the photocuring reaction of acrylate polymers.

[0030] Benzoyl peroxide is used as a crosslinking agent to increase the crosslinking density and stability of OCA optical adhesive.

[0031] Light release protective film and heavy release protective film protect the adhesive layer during coating and curing to prevent contamination and damage.

[0032] The combined effect of these substances enables the low-dielectric OCA optical adhesive of the present invention to have good adhesion, aging resistance, optical properties and mechanical properties, and is suitable for high-end applications such as foldable display terminals.

[0033] Compared with the prior art, it has the following beneficial effects: 1) The present invention successfully reduces the dielectric constant of OCA optical adhesive through a specific chemical formula and preparation method, which is of great significance for improving touch sensitivity and signal transmission speed, especially in the field of folding display technology.

[0034] 2) The present invention introduces a modified functional agent, and the OCA optical adhesive of the present invention exhibits better peeling force, impact resistance and bonding strength. The flexible siloxane main chain and rigid polyphenylene ether side chain structure in the modified functional agent, as well as the physical cross-linking network formed by the comb-shaped polyether molecular chain of the side chain and the acrylic polymer molecular chain, significantly improve the cohesion and aging resistance of the adhesive.

[0035] 3) The OCA optical adhesive of the present invention has excellent optical transparency and UV resistance while maintaining a low dielectric constant, which is essential for improving the reliability and durability of the product. In addition, by precisely controlling the formula and curing conditions, the OCA optical adhesive of the present invention exhibits better bonding performance and environmental aging resistance in practical applications, thereby expanding its application range in high-end display technology. DETAILED DESCRIPTION

[0036] Main sources of substances: Antioxidant 168 was purchased from BASF (China) Co., Ltd.

[0037] Photoinitiator 1173 was purchased from BASF (China) Co., Ltd.

[0038] 2,6-Bis(hydroxymethyl)-1,4-dimethoxybenzene, CAS number: 78840-04-7.

[0039] Pentafluorophenylpropyltrimethoxysilane, CAS number: 303191-26-6.

[0040] 4-(1-Hydroxyethyl)-6-methyl-1,2,3,5-benzene, CAS number: 108192-46-7.

[0041] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0042] The design idea of ​​the present invention is to develop a low-dielectric OCA optical adhesive and its preparation method and application. By introducing a modified functional agent with a flexible siloxane main chain and a rigid polyphenylene ether side chain, the mechanical properties and aging resistance of the OCA optical adhesive are enhanced while maintaining low dielectric properties to meet the demand for high-performance OCA optical adhesive in folding display technology. This modified functional agent achieves a significant improvement in the peeling force, impact resistance and bonding strength of the OCA optical adhesive by finely regulating the molecular structure and chemical composition, expanding its application range in high-end display technology. Example

[0043] A method for preparing a low dielectric OCA optical adhesive is as follows: Step 1: First, 70 g of butyl acrylate, 20 g of allyl 2-hydroxypropionate, 10 g of 2-ethylhexyl acrylate, 0.05 g of α,α-dimethoxy-α-phenylacetophenone and 0.04 g of n-dodecyl mercaptan were mixed in a three-necked flask, stirred for 30 minutes in a nitrogen environment, and then irradiated with a 365 nm wavelength ultraviolet lamp for 2 minutes, with an ultraviolet light energy of 800 mJ / cm 2 , obtaining an acrylate polymer; Step 2: 100 g of the acrylate polymer prepared in step 1, 5 g of the modified functional agent, 7 g of 1-ethyl cyclohexyl acrylate, 0.4 g of 1,10-decanediol diacrylate, 8 g of 3-isobornyl cyclohexyl acrylate, 10 g of diethylene glycol monoacrylate, 0.2 g of hydrogenated rosin, 0.3 g of antioxidant 168, 0.8 g of photoinitiator 1173 and 0.8 g of dibenzoyl peroxide were mixed and allowed to stand to eliminate bubbles, and then an automatic coating machine was used to evenly coat an 80 um thick adhesive layer on the light release protective film, and covered with a layer of heavy release protective film, wherein the light release protective film had a thickness of 40 μm and a release force of 5 g / in; the heavy release protective film had a thickness of 90 μm and a release force of 25 g / in; ultraviolet light with a wavelength of 365 nm was used for curing for 2 minutes, and the ultraviolet light energy was 1000 mJ / cm 2 , thereby obtaining a low dielectric OCA optical adhesive.

[0044] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of triglycidyl p-aminophenol is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent. Example

[0045] The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0046] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 4-(1-hydroxyethyl)-6-methyl-1,2,3,5-benzene and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of triglycidyl p-aminophenol is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent. Example

[0047] The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0048] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 6g of (3,5-dichlorophenoxy)triisopropylsilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, and then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of triglycidyl p-aminophenol is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent. Example

[0049] The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0050] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of resorcinol diglycidyl ether is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent. Example

[0051] The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0052] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate the mixture, 15 g of glycidyl methacrylate is added and heated to 140° C. for 10 hours, and the mixture is washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent.

[0053] Comparative Example 1 The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0054] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-dimethylhydroquinone and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of triglycidyl p-aminophenol is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent.

[0055] Comparative Example 2 The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0056] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of 4-amino-3-hydroxypyridine hydrochloride to 130°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of ethylene oxide is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent.

[0057] Comparative Example 3 The preparation method of a low dielectric OCA optical adhesive is basically the same as that of Example 1, the only difference being the preparation method of the modified functional agent.

[0058] The preparation method of the modified functional agent is as follows: S1, 300g of dimethyl sulfoxide, 150g of methanol, 15g of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 6g of pentafluorophenylpropyltrimethoxysilane were mixed in a flask, 7g of potassium carbonate was added, and the mixture was heated to 150°C for azeotropic dehydration for 2 hours, then heated to 180°C for 10 hours, then cooled and 400g of anhydrous ethanol was added, and a filter cake was obtained by suction filtration and washing, and finally dried to obtain a pretreated product; S2, heating 40g of pyridine hydrochloride to 160°C in a flask, adding 6g of the pre-treated product prepared in step S1, and continuing to heat to 230°C for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated product; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 20 mg of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 15 g of triglycidyl p-aminophenol is added and heated to 140° C. for 10 hours, washed with 0.3 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent.

[0059] Comparative Example 4 A method for preparing a low dielectric OCA optical adhesive is as follows: Step 1: First, 70 g of butyl acrylate, 20 g of allyl 2-hydroxypropionate, 10 g of 2-ethylhexyl acrylate, 0.05 g of α,α-dimethoxy-α-phenylacetophenone and 0.04 g of n-dodecyl mercaptan were mixed in a three-necked flask, stirred for 30 minutes in a nitrogen environment, and then irradiated with a 365 nm wavelength ultraviolet lamp for 2 minutes, with an ultraviolet light energy of 800 mJ / cm 2 , obtaining an acrylate polymer; Step 2: 100 g of the acrylate polymer prepared in step 1, 7 g of 1-ethyl cyclohexyl acrylate, 0.4 g of 1,10-decanediol diacrylate, 8 g of 3-isobornyl cyclohexyl acrylate, 10 g of diethylene glycol monoacrylate, 0.2 g of hydrogenated rosin, 0.3 g of antioxidant 168, 0.8 g of photoinitiator 1173 and 0.8 g of dibenzoyl peroxide were mixed and allowed to stand to eliminate bubbles, and then an automatic coating machine was used to evenly coat an 80 um thick adhesive layer on the light release protective film, and covered with a layer of heavy release protective film, wherein the light release protective film had a thickness of 40 μm and a release force of 5 g / in; the heavy release protective film had a thickness of 90 μm and a release force of 25 g / in; ultraviolet light with a wavelength of 365 nm was used for curing for 2 minutes, and the ultraviolet light energy was 1000 mJ / cm 2 , thereby obtaining a low dielectric OCA optical adhesive.

[0060] Test Example 1 Peel force test According to the test procedure of the national standard GB / T 2792-2014 "Test method for peel strength of adhesive tape", the samples are prepared as follows: First, cut the cured low-dielectric OCA optical adhesive into adhesive tapes with a width of 25mm and a length of more than 250mm, and stick them on a clean and smooth steel surface. Next, use a 1kg roller to compact the sample three times at a rate of 200mm / min, and let it stand for 20 minutes after compaction. After that, fold the free end of the sample 180° and fix it on the test equipment. Perform a peel strength test at a speed of 300mm / min, and record the peel force value and the ambient temperature and humidity during the test. Finally, calculate the average value of the peel force test results of the middle part of the low-dielectric OCA optical adhesive to be tested. The specific test data is shown in Table 1.

[0061] Table 1 Experimental protocol Peel force / N Example 1 20.5 Example 2 18.4 Example 3 19.5 Example 4 19.4 Example 5 19.0 Comparative Example 1 18.2 Comparative Example 2 18.9 Comparative Example 3 19.8 Comparative Example 4 16.7 Test Example 2 Aging test When evaluating the aging resistance, the low dielectric OCA optical adhesive samples prepared in Examples 1-5 and Comparative Examples 1-4 were placed in a xenon lamp aging test chamber under simulated daylight conditions. The light source intensity of the test chamber was set to 0.68W, the wavelength was 340nm, and the temperature was maintained at 80°C. After 1000 hours of continuous exposure, the samples were taken out, and the color change of the samples was measured using a colorimeter, with the yellowing value and the color difference value (△E) as evaluation indicators. The lower the color difference value, the better the yellowing resistance of the sample, thereby reflecting better aging resistance. The test results are shown in Table 2.

[0062] Table 2 Experimental protocol Yellowing value (△E) Example 1 0.21 Example 2 0.58 Example 3 0.34 Example 4 0.32 Example 5 0.38 Comparative Example 1 0.62 Comparative Example 2 0.40 Comparative Example 3 0.30 Comparative Example 4 0.93 It can be seen from the data in Tables 1-2 that, compared with Examples 1-5 and Comparative Examples 1-4, the low dielectric OCA optical adhesive prepared in Example 1 has the largest peeling force and the best aging resistance.

[0063] The 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene used in Example 1 contains two hydroxymethyl groups and two phenoxy groups in its molecular structure, which provides more active sites and stronger intermolecular forces, which helps to form more crosslinks and entanglements in the polymer network. This structure not only enhances the cohesion of the polymer, but also improves its compatibility with the acrylate polymer, which manifests itself as higher peeling force and better aging resistance on a macro scale. In contrast, 4-(1-hydroxyethyl)-6-methyl-1,2,3,5-benzene in Example 2 and 2,6-dimethylhydroquinone in Comparative Example 1 lack sufficient active sites and polar groups, and cannot form intermolecular interactions of the same strength, so they are not as good as Example 1 in terms of peeling force and aging resistance. This difference in molecular structure directly affects the mechanical properties and environmental aging resistance of the final OCA optical adhesive.

[0064] The main difference in molecular structure between the pentafluorophenylpropyltrimethoxysilane used in Example 1 and the (3,5-dichlorophenoxy)triisopropylsilane used in Example 3 is that the former contains five fluorine atoms, while the latter contains two chlorine atoms. Fluorine atoms have a higher electronegativity than chlorine atoms, which makes the pentafluorophenyl group have a stronger electron attraction ability, thereby enhancing the etherification reaction activity with 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene. In Example 1, the strong electron attraction of pentafluorophenylpropyltrimethoxysilane may promote the combination with hydroxyl groups and enhance the stability of ether bonds, thereby improving the cohesion and bonding properties of the adhesive. In contrast, although the chlorine atoms in (3,5-dichlorophenoxy)triisopropylsilane can also provide a certain electron attraction effect, its effect is not as significant as that of fluorine atoms, so it is not as good as pentafluorophenylpropyltrimethoxysilane in terms of peeling force and aging resistance. This difference in molecular structure leads to significant differences in the final OCA optical adhesive performance of the two modified functional agents.

[0065] The triglycidyl p-aminophenol used in Example 1 can effectively react with other components in the functional modification agent to form a highly cross-linked network structure because it contains three epoxy groups in its molecular structure. This highly cross-linked structure not only enhances the cohesive force of the adhesive, but also improves its resistance to external stress, thereby significantly improving the peeling force and aging resistance. In contrast, the resorcinol diglycidyl ether in Example 4 contains two epoxy groups, the glycidyl methacrylate in Example 5 contains one epoxy group, and the ethylene oxide in Comparative Example 2 has only one epoxy group. Although these substances can also participate in the polymerization reaction, due to the small number of epoxy groups, the cross-linked network density formed is low, so its cross-linking density and network strength are not as good as triglycidyl p-aminophenol, resulting in the final OCA optical adhesive being inferior to Example 1 in terms of peeling force and aging resistance.

Claims

1. A method for preparing a low dielectric OCA optical adhesive, characterized in that: The method is as follows, in parts by weight: Step 1, first, 60-80 parts of butyl acrylate, 15-25 parts of allyl 2-hydroxypropionate, 8-12 parts of 2-ethylhexyl acrylate, 0.04-0.06 parts of α,α-dimethoxy-α-phenylacetophenone and 0.03-0.05 parts of n-dodecyl mercaptan are uniformly mixed, stirred in a nitrogen environment for 20-40 minutes, and then irradiated with an ultraviolet lamp to obtain an acrylate polymer; Step 2: 80-120 parts of the acrylate polymer prepared in step 1, 4-6 parts of the functional modification agent, 5-10 parts of 1-ethyl cyclohexyl acrylate, 0.3-0.5 parts of 1,10-decanediol diacrylate, 5-10 parts of 3-isobornyl cyclohexyl acrylate, 8-12 parts of diethylene glycol monoacrylate, 0.1-0.3 parts of hydrogenated rosin, 0.2-0.4 parts of antioxidant, 0.5-1 parts of photoinitiator and 0.5-1 parts of initiator are mixed and allowed to stand to eliminate bubbles, and then a 60-100 um thick adhesive layer is evenly coated on the light release protective film using an automatic coating machine, and a layer of heavy release protective film is covered, and ultraviolet light is used for curing to obtain a low dielectric OCA optical adhesive.

2. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The ultraviolet light irradiation in step 1 is to use an ultraviolet light with a wavelength of 350-400nm for 1-5 minutes, and the ultraviolet light energy is 600-1000mJ / cm 2 .

3. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The UV curing in step 2 is performed by using UV light with a wavelength of 350-400 nm for 1-5 minutes, and the UV light energy is 800-1200 mJ / cm 2 .

4. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1076, antioxidant 168, antioxidant 703, and antioxidant 1010.

5. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The photoinitiator is at least one of photoinitiator 1173 and photoinitiator 754 .

6. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The light release protective film has a thickness of 30-60 μm and a release force of 4-6 g / in.

7. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The heavy release protective film has a thickness of 50-100 μm and a release force of 20-30 g / in.

8. The method for preparing the low dielectric OCA optical adhesive according to claim 1, characterized in that: The preparation method of the modified functional agent is as follows, in parts by weight: S1. Add 5 to 10 parts of potassium carbonate to 200 to 400 parts of dimethyl sulfoxide, 120 to 180 parts of methanol, 12 to 18 parts of 2,6-bis(hydroxymethyl)-1,4-dimethoxybenzene and 5 to 7 parts of pentafluorophenylpropyltrimethoxysilane, heat to 140 to 160° C. for azeotropic dehydration for 1 to 3 hours, then heat to 160 to 200° C. for 5 to 15 hours, then cool and add 300 to 500 parts of anhydrous ethanol, obtain a filter cake by suction filtration and washing, and finally dry to obtain a pretreated product; S2, heating 30-50 parts of 4-amino-3-hydroxypyridine hydrochloride to 120-140° C. in a flask, adding 5-7 parts of the pre-treated material prepared in step S1, and continuing to heat to 220-240° C. for treatment. After the treatment is completed, filtering and washing with boiling water, and then drying to obtain a post-treated material; S3. In a reaction kettle, the post-treated product prepared in step S2 is mixed with 0.01-0.03 parts of potassium hydroxide, nitrogen is introduced to evacuate the air and then evacuate, 12-18 parts of triglycidyl p-aminophenol are added and heated to 120-180° C. for 5-15 hours, washed with 0.2-0.4 mol / L hydrochloric acid and water respectively, and dried to obtain a modified functional agent.

9. A low dielectric OCA optical adhesive, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. An application of the low dielectric OCA optical adhesive as claimed in claim 9, characterized in that: Applicable to foldable display terminals.

Citation Information

Patent Citations

  • Anti-UV (ultraviolet) OCA (optical clear adhesive) and preparation method thereof

    CN113322028A